Uso ilegítimo de armas letales y de letalidad reducida contra manifestantes en Bangladesh - Amnesty International (Amnistía Internacional, 2024)
“Amnistía Internacional insta al Gobierno de Bangladesh y a sus organismos a que respeten el derecho a la protesta y pongan fin a la represión violenta.”
Bangladesh

L’analyse de nouvelles vidéos et photos confirme l’usage illégal par la police d’armes meurtrières et à létalité réduite contre les manifestant·e·s - Amnesty International (Amnesty International, 2024)
La vérification et l’analyse des preuves vidéo et photographiques qui filtrent hors du Bangladesh dressent un sombre tableau.
Bangladesh

Further video and photographic analysis confirm police unlawfully used lethal and less-lethal weapons against protesters - Amnesty International (Amnesty International, 2024)
Amnesty International urges the Government of Bangladesh and its agencies to respect the right to protest and end this violent crackdown.
Bangladesh

Sweeping pattern of systematic attacks and restrictions undermine peaceful protest - Amnesty International (Amnesty International, 2024)
Across Europe, the right of peaceful assembly is coming under severe attack as states increasingly stigmatize, criminalise and crack down on peaceful protesters, imposing unjustified and punitive restrictions and resorting to ever more repressive means to stifle dissent, said Amnesty International in a new report.
Europe